Ethnoveterinary utilization of medicinal plants in Ghamot National Park Western Himalayas of Azad Jammu and Kashmir, Pakistan - Jahangeer, Muhammad; Siddique Awan, Muhammad; Shakeel Awan, Muhammad; Minhas, Riaz Aziz; Saleem, Mir Muhammad; Ali, Usman; Sudhzoi, Abid (Ethnobotany Research and Applications, 2024)
Background: The local communities in Pakistan possess extensive traditional knowledge about indigenous medicinal plants, which has been passed down through generations for centuries. However, this invaluable ethnic knowledge is currently facing a threat to its preservation. In Pakistan, research on medicinal plants predominantly centers on documenting the local flora and its applications. The indigenous population, with ancestral wisdom, holds traditional insights into the uses of regional plants. Ethno-veterinary medicine encompasses the collective beliefs, expertise, techniques, and customs within communities concerning animal welfare, particularly prominent in rural settings where it serves as a primary approach to livestock treatment. This study aims to address the existing knowledge gap by documenting ethno-veterinary knowledge from this untapped area. The specific objectives are focused on recording the essential ethno-veterinary applications of local plant species by mountain populations in treating livestock ailments and disorders. Methods: Data regarding the use of ethno-medicinal plants for treating livestock ailments were gathered through a semi-structured questionnaire, one-on-one interviews, and group discussions. From 2022 to 2023, we interviewed 124 individuals about 28 plant species, with the majority of ethno-veterinary data coming from respondents in the 40–69 age groups. The frequency of citation was determined to assess how often a specific plant species was mentioned for treating veterinary diseases. Additionally, the Use Value (UV) for each species was computed using UV = FC/N. Results: The research identified 28 medicinal plants from 22 different plant families used for treating 23 distinct livestock ailments. These plants comprised 21 herbs (75% of the total), 5 shrubs (17.85%), and 2 trees (7.14%). The dominant plant family was Asteraceae (3sp.). Roots (46%) were the primary plant part used in medicines, and paste (19 sp.) was the most common herbal formulation method. Most medicinal plants (8) were employed to cure digestive system diseases such as dysentery and indigestion. A comparison of the collected medicinal plants and related indigenous medicinal knowledge was made with previously published work on surrounding areas. Conclusion: This study assumes a vital role in preserving indigenous plant-based knowledge from potential oblivion and introduces new ethno-veterinary applications in the region. Further investigations involving phytochemical and pharmacological assessments are necessary to isolate active compounds and evaluate plant efficacy against specific veterinary diseases, both in vitro and in vivo. Comprehensive toxicological studies are also imperative to ensure the safe and secure utilization of documented ethno-medicines. Keywords: Ethno-veterinary, Medicinal plants, Western Himalayas, Ghamot National Park